Mercury Exposure Analyses Amongst Dene and Métis Communities of the Northwest Territories - Fung, Leicester (University of Waterloo, 2018)
Background: Fish is an important food source for many Indigenous communities within the Dehcho and Sahtú regions of Northwest Territories (NWT). However, environmental toxicants, such as mercury (Hg), can bioaccumulate and biomagnify to reach detectable levels in fish, particularly among predatory fish species. From a public health perspective, Hg exposure and biomonitoring assessments are invaluable assets that can highlight potential risk factors and evaluate risks associated with Hg toxicity. With the current body of knowledge, exposure assessment models conservatively account for Hg bioaccessibility in fish to be 100% because of the limited information available. Past literature have also noted statistical differences in Hg bioaccessibility with respect to food source as well as food preparation methods. As such, there is a need for more Hg biomonitoring and Hg bioaccessibility assessments to elucidate the relationships between dietary and demographic determinants with respect to Hg exposure. Objectives: Hg biomonitoring component. 1) To determine internal Hg exposure levels (blood and hair) from six Indigenous communities in the Dehcho and Sahtú regions of NWT. 2) To conduct t-test analysis for internal Hg exposure levels with respect to sex. 3) To construct simple linear regression models between internal Hg exposure levels with the following factors: i) age ii) non-piscivorous fish consumption iii) piscivorous fish consumption. Hg bioaccessibility component. 1) To characterize Hg concentrations for uncooked and dried by smoking (dried/smoked) lake whitefish (Coregonus clupeaformis). 2) To determine Hg bioaccessibility in uncooked and dried/smoked lake whitefish. 3) To conduct t-test analysis to determine Hg concentration and Hg bioaccesibility differences between uncooked and dried/smoked whitefish. Methods: Hg biomonitoring component. 150 Dene and Métis participants, between the ages of 6-79, were recruited from Deline, Fort Providence, Hay River Reserve, Kakisa, West Point First Nation and Jean Marie ...